2016
DOI: 10.1016/j.ymgme.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cases with 3-methylcrotonyl-CoA carboxylase (3-MCC) deficiency - Report from the Inborn Errors of Metabolism Information System

Abstract: Introduction 3-Methyl crotonyl CoA carboxylase (3MCC) deficiency is an inborn error of leucine metabolism whose detection was increased with the advent of expanded newborn screening. While most NBS-identified infants appear clinically normal, prior studies suggest a possible increased risk for developmental or metabolic abnormalities. As yet, no predictive markers are known that can identify children at risk for biochemical or developmental abnormalities. Method All available 3-MCC cases diagnosed by newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…, 2009 ). In addition, a recent study pointed out that the C5-OH level found in newborn screening is not sufficient for diagnostic or predictive purposes ( Forsyth et al. , 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2009 ). In addition, a recent study pointed out that the C5-OH level found in newborn screening is not sufficient for diagnostic or predictive purposes ( Forsyth et al. , 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical phenotype of 3-MCC deficiency is highly variable, ranging from severe neurological abnormalities and death in infancy ( Baykal et al , 2005 ) to asymptomatic adults ( Dantas et al , 2005 ; Forsyth et al , 2016 ). A severe presentation of 3-MCC deficit may include the Reye-like illness, ketoacidosis, hypoglycemia, hyperammonemia, psychomotor retardation, seizures, symptoms of cardiorespiratory failure and coma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic mothers with 3-methylcrotonyl glycinuria have been identified by detection of abnormal neonatal screening performed in their healthy offspring, having passed the abnormal metabolites to their infants through the placenta. 29 In case of normal mother's results, biotin and especially biotinidase activity in DBS should be performed. 30 Here, we may underline that biotin blood levels were not measured, whereas biotinidase activities were normal in neonates (unpublished data).…”
Section: Groupmentioning
confidence: 99%
“…A report describing the use of the IBEM-IS to illustrate the outcomes of children with 3-methylcrotonyl-CoA carboxylase deficiency was recently published. 3 The IBEM-IS database was also used to describe outcomes and genotype-phenotype correlations of individuals with very-long-chain acyl-CoA dehydrogenase deficiency. 4 These are just the beginning; the potential of IBEM-IS to inform NBS practices is substantial.…”
mentioning
confidence: 99%